Optimized Phase-Generated Carrier Demodulation Algorithm for Membrane-Free Fabry-Pérot Acoustic Sensor with High Sensitivity - Yang, Yang; Zhao, Xinyu; Zheng, Yongqiu; Cui, Juan; Zhao, Dongqing; Zheng, Zhixuan; Cao, Yan; Xue, Chenyang (Micromachines (Basel), 2025)
Demodulation of fiber optic Fabry–Pérot (F-P) acoustic sensors with high sensitivity and a large dynamic range continues to pose significant challenges. In this paper, we propose an advanced phase-generated carrier (PGC) demodulation algorithm, applied innovatively to membrane-free F-P acoustic sensors operating under high sound pressure. The algorithm optimizes acoustic demodulation results by adjusting the mixing phase delay, achieving the best signal to noise and distortion ratio (SINAD) and total harmonic distortion (THD) (<1%). Additionally, by introducing the cosine component of the acoustic signal obtained directly after filtering the interference signal, into the demodulation algorithm process, the sensitivity of the sensor at high sound pressure is significantly improved. The experimental results show that the ameliorated algorithm obtains a demodulation sensitivity of 34.95 μrad/Pa and a THD of 0.87%, both of which are superior to traditional PGC demodulation algorithms under the same experimental conditions. At the same time, the minimum detectable sound pressure of 129.73 mPa/Hz1/2 was obtained, and the sound pressure tested in the experiment at a frequency of 1 kHz was as high as 3169.78 Pa (164 dB). With the proposed algorithm, the flatness of the frequency response is ±0.82 dB from 100 Hz to 33 kHz, and a dynamic range of up to 102.6 dB was obtained, making it relevant in the field of aerospace acoustic measurements.